80.7k views
3 votes
ASAP! I really need help with this question! No nonsense answers, and please attach the solution.

ASAP! I really need help with this question! No nonsense answers, and please attach-example-1

2 Answers

1 vote

Answer:


\boxed{\sf Option \ 4}

Explanation:


√(2x-3) +x=3

Subtract x from both sides.


√(2x-3) +x-x=-x+3


√(2x-3)=-x+3

Square both sides.


( √(2x-3))^2 =(-x+3)^2


2x-3=x^2-6x+9

Subtract x²-6x+9 from both sides.


2x-3-(x^2-6x+9 )=x^2-6x+9-(x^2-6x+9)


-x^2 +8x-12=0

Factor left side of the equation.


(-x+2)(x-6)=0

Set factors equal to 0.


-x+2=0\\-x=-2\\x=2


x-6=0\\x=6

Check if the solutions are extraneous or not.

Plug x as 2.


√(2(2)-3) +2=3\\ √(4-3) +2=3\\√(1) +2=3\\3=3

x = 2 works in the equation.

Plug x as 6.


√(2(6)-3) +6=3\\ √(12-3) +6=3\\√(9) +6=3\\3+6=3\\9=3

x = 6 does not work in the equation.

User John Gilmer
by
5.4k points
7 votes

Answer:

option d

Explanation:


√(2x-3)+x = 3\\\\√(2x-3) = 3 -x\\

Square both sides


(√(2x-3))^(2)=(3-x)^(2)\\\\\\2x-3=9-6x+x^(2)\\\\0=x^(2)-6x + 9 - 2x + 3\\ {Add like terms}


x^(2) - 8x + 12 = 0

Sum = -8

Product = 12

Factors = -2 , - 6

x² - 2x - 6x + (-2) * (-6) = 0

x(x -2) - 6(x -2) = 0

(x -2) (x - 6) = 0

x - 2 =0 ; x - 6 = 0

x = 2 ; x = 6

roots of the equation : 2 , 6

But when we put x = 6, it doesn't satisfies the equation.

When x = 6,


√(2x-3) + x = 3\\\\√(2*6-3)+6 = 3\\\\√(12-3)+6=3\\\\√(9)+6=3\\\\

3 + 6≠ 3

Therefore, x = 2 but x = 6 is extraneous

User Kreys
by
6.7k points